(untitled) (Research, Society and Development, 2020)
Success in professional careers has always been guided by the individual’s technical skills (hard skills) necessary to solve everyday problems. Recently, the development of human skills, also known as "soft skills", has gained prominence in interpersonal and corporate relationships. What draws attention is that such skills are not yet part of most regular vocational training. The aim of the present study was to understand the level of self-awareness among students of basic, technical and technological education participating in academic study groups about their behaviors in relation to soft skills Evaluation was applied through a questionnaire where the skills were grouped into three distinct groups: Group 1: time management and organization; Group 2: entrepreneurship and ability to perform tasks; and Group 3: self-knowledge and mentality. The students’ responses were compared to the perception of the study group’s advisors regarding the real capacity of each student to achieve the expected goal in relation to the item evaluated based on the relationship developed between the student and the advisor. In view of the results, it can be observed that the students’ self-perception of their own personal skills is a factor to be worked on in the classroom, or even in extracurricular projects, so that, from increasing awareness of the need for improvement, students develop, in addition to traditional technical skills, your personal skills that are so necessary for the contemporary job market, and thus move towards evolution and professional development.